Crystal Structure of Bismuth-Containing Samarium Iron–Aluminium Borates Sm1−xBixFe3−yAly(BO3)4 (x = 0.05–0.07, y = 0–0.28) in the Temperature Range of 25–500 K - Ekaterina S. Smirnova; Olga A. Alekseeva; Vladimir V. Artemov; Timofei A. Sorokin; Dmitry N. Khmelenin; Ekaterina V. Sidorova; Kirill V. Frolov; Irina A. Gudim (Crystals, 2023)
Structural features of new mixed bismuth-containing samarium iron–aluminium borate single crystals Sm1−xBixFe3−yAly(BO3)4 (x = 0.05–0.07, y = 0–0.28) were studied using X-ray diffraction analysis based on aluminium content and temperature in the range 25–500 K. The crystals were grown using the solution-in-melt technique with Bi2Mo3O12 in a flux. The composition of the single crystals was analyzed using energy-dispersive X-ray fluorescence and energy-dispersive X-ray elemental analysis. Temperature dependencies of Sm1−xBixFe3−yAly(BO3)4 unit-cell parameters were studied. Negative thermal expansion was identified below 100 K and represented by characteristic surfaces of the thermal expansion tensor. (Sm,Bi)–O, (Sm,Bi)–(Fe,Al), (Fe,Al)–(Fe,Al), and (Fe,Al)–O interatomic distances decreased with the addition of aluminium atoms. An increase in the (Fe,Al)–(Fe,Al) intrachain bond length at low temperatures in the magnetically ordered state weakened this bond, whereas a decrease in the (Fe,Al)–(Fe,Al) interchain distance strengthened super-exchange paths between different chains. It was found that the addition of aluminium atoms influenced interatomic distances in Sm1−xBixFe3−yAly(BO3)4 much more than lowering the temperature from 293 K to 25 K. The effect of aluminium doping on magnetoelectric properties and structural symmetry of rare-earth iron borates is also discussed.